THE EFFECT OF UNDERSTANDING OF TAX REGULATIONS, TAX SANCTIONS AND TAX RATES ON SMALL MEDIUM ENTERPRISES TAX COMPLIANCE IN BANTUL REGENCY - Hana Indah Sari; Kunti Sunaryo; Indra Kusumawardhani (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2021)
Small Medium Enterprises (SME) in Indonesia absorb 96% of the workforce and contribute 60% of Indonesia's GDP. This shows the magnitude of potential tax revenue for SME. Government Regulation No. 23 of 2018 which changes the rates to 0.5% is expected to make it easier for SME to comply with their tax obligations. The purpose of this study was to look at the influence between Understanding of Tax Regulations, Tax Sanctions, and Tax Rates on SME Tax Compliance in Bantul Regency This research is used descriptive method.The population in this study were all SME actors in Bantul Regency, and the sample was 100 SME actors in Bantul Regency. The sampling technique used is convenience sampling. The test results of this study indicate that Understanding of Tax Regulations and Tax Rates do not affect the SME Tax Compliance in Bantul Regency. Tax sanctions affect SME Tax Compliance in Bantul Regency